Identification and Morphological Characterization of Sugar Palm Plants (Arenga pinnata Merr.) Growing on Different Altitudes - Hasibuan, Halimatus Syahdia; Wisnubroto, Muhammad P; Edwin, Edwin; Rezki, Dewi; Yulistriani, Yulistriani (Universitas Pattimura, 2023)
Trees of sugar palm (Arenga pinnata Merr.) can grow at an altitude of 0-1400 m above sea level. The best growth of the trees is at an altitude of 500-700 m above sea level. Sugar palm trees also have a wide adaptability to various environmental conditions. The purpose of this research was to determine the morphological characteristicss of sugar palm plants grown at an altitude of 500, 650, and 900 m above sea level so that the kinship relationship can be known. This research was conducted at three altitudes in Lareh Sago Halaban District, Lima Puluh Kota Regency, West Sumatra, namely Nagari Labuah Gunung (altitude 900 m above sea level), Nagari Bukik Sikumpa (altitude 650 m above sea level), and Nagari Tanjung Gadang (altitude 500 m above sea level) from July to August 2023. The method used was a survey with a purposive sampling technique. Identification was carried out on 36 morphological characters, including stems, leaves, fibers, fruits, and seeds. The data obtained were analyzed for their diversity and similarity. The results of the identification and characterization of qualitative and quantitative morphological characters at three different altitudes showed a relatively narrow diversity value. The overall morphological characters of the sugar palm plants were divided into 2 large groups with a coefficient value of 0.72 or 72% similarity distance.